1986
DOI: 10.1111/j.1445-2197.1986.tb02342.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin Blood Flow Measurement With Xenon‐133 to Predict Healing of Lower Extremity Amputations

Abstract: Many techniques have been proposed to help the surgeon select the most distal amputation level that will heal. Skin blood flow measurement with xenon-133 (133Xe) is one of the best documented predictors of amputation healing, but the lowest flow consistent with healing has not been agreed upon. Our early experience with the method is reported. Skin blood flow was measured in 16 patients undergoing 17 lower extremity amputations. Twelve amputations healed (mean skin blood flow 3.69 ? 2.73 m1/100 g of tissue/min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
1

Year Published

1990
1990
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…Previous studies have attempted to determine the extent of ischaemia present in the skin at various levels of the leg in patients with CLI. A variety of techniques have been used including radioisotope clearance studies [33,34], laser Doppler flowmetry [35,36] and transcutaneous oximetry (TcPO # ) [37,38]. However, few studies have shown agreement between these methods of assessment of ischaemia and the clinical outcome of the patient.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have attempted to determine the extent of ischaemia present in the skin at various levels of the leg in patients with CLI. A variety of techniques have been used including radioisotope clearance studies [33,34], laser Doppler flowmetry [35,36] and transcutaneous oximetry (TcPO # ) [37,38]. However, few studies have shown agreement between these methods of assessment of ischaemia and the clinical outcome of the patient.…”
Section: Discussionmentioning
confidence: 98%
“…A variety of techniques have been used including radioisotope clearance studies [33,34], laser Doppler flowmetry [35,36] and transcutaneous oximetry (TcPO # ) [37,38]. Previous studies have attempted to determine the extent of ischaemia present in the skin at various levels of the leg in patients with CLI.…”
Section: Discussionmentioning
confidence: 99%
“…Malone et al (1981) found healing in all the cases with skin blood flow over 2.6 mL/100 g tissue/min and healing in half the cases when the flow was between 2 and 2.6 mL. Harris et al (1986) reported healing when skin blood flow was more than 1 mL/100 g tissue/min. However, Holloway and Burgess (1978) were not able to document a clear-cut end point for skin blood flow above which all the amputations healed, and in a more recent investigation Malone et al (1987) found skin blood flow unreliable for selecting the amputation level.…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, skin blood flow has proved to be of value in selecting the level for amputation (Moore 1973, Harris et al 1986, Malone et al 1981), but there is disagreement concerning the lower limit of skin blood flow. Malone et al (1981) found healing in all the cases with skin blood flow over 2.6 mL/100 g tissue/min and healing in half the cases when the flow was between 2 and 2.6 mL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation